Modelling of the electrohydraulic full active vehicle suspension - KONIECZNY, J. (Engineering Transactions, 2008)
The study investigates various models of vehicle suspensions. A quarter-vehicle full active suspension is chosen for further analysis. A mathematical model, governed by nonlinear differ- ential equations, is proposed that takes into account dynamic properties of an electrohydraulic actuator. The mathematical model being implemented, it was expressed in terms of the state variables. In part two, the physical model was implemented and parametric identification pro- cedure was applied. Phenomenological model simulation data are compared with results of experimental testing of a full, active vehicle suspension. The final section is focused on static and dynamic properties of an open-loop system (without a controller) determined on the basis of obtained models.